Visual problems in the elderly population and implications for services. Issue 6836 (9th May 1992) - Wormald, R. P.; Wright, L. A.; Courtney, P.; Beaumont, B.; Haines, A. P.
Abstract : OBJECTIVE–To determine the prevalence of visual disability and common eye disease among elderly people in inner London. DESIGN–Cross sectional random sample survey. SETTING–Inner London health centre. SUBJECTS–Random sample of people aged 65 and over taken from practice's computerised age-sex register. MAIN OUTCOME MEASURES–Presenting binocular Snellen 6 m distance acuity and best monocular 3 m Sonksen-Silver acuity to classify prevalence of blindness by World Health Organisation criteria (less than 3/60 in better eye) and American criteria for legal blindness (better eye equal to 6/60 or less) and of low vision by WHO criteria (best acuity 6/18) and visual impairment by American criteria (less than 6/12 or 20/40 but greater than 6/60 or 20/200 in better eye). Principal cause of visual loss by diagnosis, referral indication by cause to hospital eye service, and proportion of cases known to primary care. RESULTS–207 of 288 (72%) eligible people were examined. 17 (8%) housebound subjects were examined at home. The prevalence of blindness was 1% by WHO criteria and 3.9% by American criteria. The prevalence of low vision (WHO criteria) was 7.7%. The prevalence of visual impairment (American criteria) was 10.6%. Cataract accounted for 75% of cases of low vision. Only eight out of 16 patients with low vision were known by their general practitioner to have an eye problem. 56 subjects (27%) would probably have benefited from refraction. Comparisons with studies in the United States and Finland suggested higher rates in this sample, mainly due to the prevalence of disabling cataract. CONCLUSION–There seems to be a considerable amount of undetected ocular disease in elderly people in the community.